1994
DOI: 10.1145/198425.198426
|View full text |Cite
|
Sign up to set email alerts
|

Reaching for objects in VR displays

Abstract: This article reports the results from three experimental studies of reaching behavior in a head-coupled stereo display system with a hand-tracking subsystem for object selection. It is found that lag in the head-tracking system is relatively unimportant in predicting performance, whereas lag in the hand-tracking system is critical. The effect of hand lag can be modeled by means of a variation on Fitts' Law with the measured system lag introduced as a multiplicative variable to the Fitts' Law index of difilcult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 17 publications
3
140
0
Order By: Relevance
“…Some researchers [15,16] found that the SMALL-OF model in the 2D pointing task can be easily extended to 3D environment:…”
Section: Three Dimensional Hci Modelmentioning
confidence: 99%
“…Some researchers [15,16] found that the SMALL-OF model in the 2D pointing task can be easily extended to 3D environment:…”
Section: Three Dimensional Hci Modelmentioning
confidence: 99%
“…Dynamic errors are caused by end-to-end system delays when the tracked object moves [3,4]. In our work we ignore dynamic errors, although we are aware that these errors can be more significant than the static errors for some setups.…”
Section: Dynamic Errorsmentioning
confidence: 99%
“…Any human in the loop closed loop control system must function with latency that is below the 200ms level [3,5,8,9]. Latency above that level will result in degraded performance.…”
Section: Hardwarementioning
confidence: 99%